A modified carbon felt electrode of a vanadium redox flow battery based on joule heat regulation, a preparation method and applications thereof
Patent Information
- Application Number
- CN202611313381.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]值得注意的是,不同金属离子对配位场变化的响应敏感性存在差异:对于d5电子构型的Fe3+和Mn2+,以及d7的Co2+,配位数的降低更容易引发从低自旋向高自旋的跃迁;而对于d8的Ni2+和d10的Zn2+,其自旋态受配位场影响相对较小或保持不变
1.选择性构建吡啶氮M-N4高活性结构:本发明利用焦耳加热的毫秒级超快升温带来的极端非平衡条件,在动力学上优先驱动吡啶氮配位的M-N4结构形成,有效抑制了吡咯氮M-N4的竞争生成,大幅增加了高本征活性位点的数量。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of vanadium redox flow battery technology, and relates to a modified carbon felt electrode, its preparation method, and its application in vanadium redox flow batteries based on Joule thermal regulation. Specifically, it relates to a method for modifying a carbon felt electrode, and more particularly to a method for selectively constructing an M-N4 (M=Fe, Co, Ni, Mn, Zn) structure dominated by pyridine nitrogen coordination on the surface of a carbon felt by using a transition metal-nitrogen coordination precursor combined with transient Joule heating technology, and improving the electrochemical performance of the electrode by inducing unsaturated coordination through extreme thermal shock to regulate the 3d spin state of the metal center. Background Technology
[0002] Vanadium redox flow batteries (VRFBs) have broad application prospects in large-scale energy storage due to their advantages such as long lifespan, safety, and independently designable capacity. Carbon felt, with its three-dimensional porous structure, high specific surface area, and excellent chemical stability, is one of the most commonly used electrode materials for VRFBs. However, the poor hydrophilicity and few electrochemical active sites of pristine carbon felt lead to sluggish vanadium ion redox reaction kinetics, limiting the battery's voltage efficiency and power density.
[0003] In recent years, the introduction of transition metal-nitrogen-carbon (MNC, M = Fe, Co, Ni, Mn, Zn, etc.) single-atom active sites has been proven to effectively enhance electrode catalytic activity. Theoretical studies and experimental results show that M-N4 sites with pyridinic nitrogen coordination configurations exhibit the highest intrinsic catalytic activity for vanadium ion redox reactions due to their moderate metal-nitrogen bond length and optimal electronic structure. However, in conventional high-temperature pyrolysis processes, pyridinic nitrogen and pyrrolic nitrogen coexist in nitrogen-doped carbon substrates, and the pyrrolic nitrogen-coordinated M-N4 structure often dominates due to its lower formation energy, resulting in a low proportion of highly active pyridinic nitrogen M-N4 sites, which limits further improvement in electrode catalytic performance. Furthermore, the slow heating process of conventional tube furnaces keeps the system close to thermodynamic equilibrium, making it difficult to break the competitive balance between pyridinic nitrogen M-N4 and pyrrolic nitrogen M-N4, and prolonged high temperatures easily lead to metal atom aggregation.
[0004] More importantly, the intrinsic activity of a catalyst also strongly depends on the 3d electron spin state of the active metal atom. According to crystal field theory, different transition metal ions (Fe... 3+ / 2+ Co 3+ / 2+ Ni 2+ Mn 3+ / 2+ Zn 2+ Due to the difference in the number of 3d electrons (d 5 ~d 10In the same four-coordinate field, they exhibit different spin state preferences. Typically, in low-spin metal centers, all 3d electrons are highly paired, and the eg orbitals are either completely or partially empty, resulting in extremely weak σ- electron-donating interactions with vanadium-oxygen intermediates. In contrast, in medium-spin or high-spin metal centers, unpaired eg electrons are present, enabling them to interact with VO2. 2+ / VO2 + The oxygen-containing orbitals form stronger hybridization, lowering the reaction energy barrier. In a perfect four-coordinate planar field (D4h symmetry), M-N4 has a strong crystal field, and the metal center usually tends to be in a low-spin state. By forming unsaturated coordination structures (such as M-N3, M-N2) or inducing distortion of the coordination field, the crystal field splitting energy can be effectively weakened, triggering spin state transitions.
[0005] It is worth noting that different metal ions exhibit varying sensitivities to changes in the ligand field: for d 5 Fe electronic configuration 3+ and Mn 2+ , and d 7 Co 2+ A decrease in coordination number makes it easier to trigger transitions from low-spin to high-spin; while for d 8 Ni 2+ and d 10 Zn 2+ The spin state of a metal is relatively little affected by the ligand field or remains unchanged. Therefore, how to achieve directional control of the spin state through extreme non-equilibrium conditions of Joule heating, based on the electronic configuration characteristics of different metal centers, is a research topic with both scientific significance and application value.
[0006] In recent years, transient Joule heating technology has gained popularity due to its ultra-fast heating (up to 10... 3 K / s ~10 4 The characteristics of ultra-fast cooling (K / s) and rapid cooling provide a breakthrough solution to the above challenges. On the one hand, the extreme non-equilibrium state during the millisecond-level heating process is expected to preferentially drive the formation of pyridine nitrogen M-N4 structure kinetically; on the other hand, ultrafast cooling can "freeze" the thermodynamically metastable unsaturated coordination structure and spin state formed at high temperature to room temperature, making it possible to simultaneously achieve efficient construction of pyridine nitrogen M-N4 and precise control of the spin state of the metal center. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for modifying vanadium battery electrode carbon felt based on transient Joule heat treatment. This method preferentially constructs highly active M-N4 (M=Fe, Co, Ni, Mn, Zn) structures with pyridine nitrogen coordination as the main component on the surface of carbon felt, and simultaneously precisely controls the 3d spin state of the metal center by inducing unsaturated coordination (M-N3, M-N2, etc.). This invention utilizes the ultrafast heating-cooling characteristics of Joule heating. On the one hand, during millisecond-level heating, it selectively enriches the pyridine nitrogen-coordinated M-N4 structure using non-equilibrium thermodynamics, significantly increasing the proportion of highly active sites. On the other hand, extreme thermal shock induces partial MN bond breakage or coordination field distortion, forming unsaturated coordination species, significantly reducing the crystal field splitting energy, and driving the central metal ion to transition from a low-spin state to a medium-spin or high-spin state, fundamentally improving the intrinsic catalytic activity of the electrode for the redox reaction of vanadium ions.
[0008] A method for preparing a modified carbon felt electrode for an all-vanadium redox flow battery based on Joule thermal regulation includes the following steps: Step 1: Pretreatment. The raw carbon felt is heat-treated in air at 200℃~800℃ for 1s-15s to remove surface impurities and introduce oxygen-containing functional groups to obtain pre-oxidized carbon felt.
[0009] Step 2: Preparation of precursor solution: Dissolve metal salt and nitrogen-containing organic ligand in solvent and stir until completely dissolved to obtain precursor impregnation solution; wherein the molar ratio of metal ion to ligand is (1:1)-(1:10).
[0010] Step 3: Immerse the pre-oxidized carbon felt obtained in Step 1 in the precursor impregnation solution of Step 2, perform the impregnation treatment under sealed conditions, and then take it out and dry it so that the precursor is evenly attached to the surface of the carbon felt fiber.
[0011] Step 4: Place the dried carbon felt from Step 3 between the two electrodes of the Joule heating device. Under inert gas protection, apply a pulsed current for instantaneous high-temperature shock, with 1-3 pulses. Control the current parameters to raise the temperature of the carbon felt to 900℃-2000℃ within 0.1s-10s and maintain it for 0.1s-5s before rapid cooling at a rate of 500℃·s. -1 ~1000℃·s -1 .
[0012] The transient Joule heating treatment in step 4 is as follows: connect the two ends of the carbon felt to a pulse discharge power supply, and generate instantaneous high temperature through pulse discharge; the MN species is an M-N4 structure with pyridine nitrogen coordination as the main component; The method constructs, in situ, a carbon felt containing MN on its surface. x The active sites of the coordination structure, under millisecond to second-level Joule heat treatment, form unsaturated MN.x Coordination, where x = 2, 3 or 4.
[0013] Furthermore, in step 1, the heat treatment in the air atmosphere is carried out in constant flow mode with a heating rate of 300°C·s. -1 ~500℃·s -1 This removes surface impurities and introduces oxygen-containing functional groups, while also improving hydrophilicity.
[0014] Furthermore, the solvent in step 2 is any one or more of ethanol, deionized water, methanol, DMF, etc., and the metal salt is one or more of Fe salt, Co salt, Ni salt, Zn salt, etc., with a concentration of 0.01M-0.05M in the precursor solution. The ligand is one or more combinations of 1,10-phenanthroline (Phen), melamine, melamine phosphate, and 2,2'-bipyridine. The precursor solution must be prepared and used immediately.
[0015] The metal salt is an Fe salt or a Co salt, and the ligand is preferably 1,10-phenanthroline (Phen), with a molar ratio of metal ion to ligand of (1:3) to (1:5). The metal salt is a Ni salt, and the preferred ligand is 2,2'-bipyridine; The ligand is a combination of two of the following: 1,10-phenanthroline (Phen), melamine, melamine phosphate and 2,2'-bipyridine, with a molar ratio of (2:1) to (2:5) between the main and auxiliary ligands.
[0016] Furthermore, in step 3, ultrasonic treatment is required during impregnation under sealed conditions, and the drying temperature is between 60°C and 80°C.
[0017] Finally, the inert gas in step 4 is argon, and the gas flow rate is 200 mL / min. -1 ~500 mL·min -1 .
[0018] The second aspect of the present invention provides a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, which is prepared by the above method. The active sites on the electrode surface include an M-N4 structure with pyridine nitrogen coordination as the main component (M is selected from one or more of Fe, Co, Ni, Mn, and Zn), and also include unsaturated coordinated M-N3 and M-N2 species. The metal center is in a medium spin state or a high spin state.
[0019] A third aspect of this invention provides the application of a modified carbon felt electrode for vanadium redox flow batteries based on Joule thermal regulation, wherein the electrode is prepared using the method described above. This electrode exhibits excellent electrochemical activity in vanadium redox flow batteries.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. Selective construction of highly active pyridine nitrogen M-N4 structure: This invention utilizes the extreme non-equilibrium conditions brought about by the millisecond-level ultra-fast heating of Joule heating to preferentially drive the formation of pyridine nitrogen-coordinated M-N4 structure in terms of kinetics, effectively suppressing the competitive generation of pyrrole nitrogen M-N4 and significantly increasing the number of highly intrinsic active sites.
[0021] 2. Precise Control of Spin State: This invention creatively utilizes the instantaneous high temperature and rapid heating and cooling characteristics of Joule heating to perform a quenching-like treatment on the MN structure formed in situ on the carbon felt. The instantaneous high temperature forces some coordinated nitrogen atoms to escape, forming nitrogen vacancies or unsaturated coordination structures (such as M-N3, M-N2). The reduction in coordination number directly weakens the crystal field splitting energy. According to crystal field theory, this will induce electron rearrangement in the central metal ion, transforming it from a lower-energy low-spin state (t2g orbital electron pairing) to a medium-spin or high-spin state with more unpaired electrons.
[0022] 3. Synergistic Gain of Pyridine Nitrogen M-N4 and Optimized Spin State: Pyridine nitrogen M-N4 provides stable single-atom anchoring and an intrinsically active basis, while the medium / high spin metal center provides more unpaired eg electrons, significantly enhancing the interaction with VO4. 2+ / VO2 + The σ-electron-donating and π-back-bonding interactions between reaction intermediates optimize the adsorption / desorption energy barriers, significantly enhancing the intrinsic electrocatalytic activity and reversibility of the vanadium ion redox reaction. This synergistic effect results in electrode performance significantly superior to the control sample, which possesses only one advantage.
[0023] 4. High efficiency and energy saving: Traditional tube furnace high-temperature carbonization takes several hours, while the Joule heating treatment of this invention is completed in just milliseconds to seconds, which greatly reduces energy consumption and time costs. Moreover, the thermal stress during the heating process helps to form a multi-level microporous structure on the fiber surface, further increasing the specific surface area. Attached Figure Description
[0024] Figure 1 Joule heating-induced ultrafast pulse process; wherein, (a) a single pulse; (b) multiple pulses; Figure 2 Test results of paramagnetic resonance (EPR) waves under different conditions; (a) test results under different pulse conditions; (b) test results of g-factor at pulse 0.4s.
[0025] Figure 3 XPS spectra of modified electrodes obtained in different embodiments; wherein, (a) Example 3, (b) Example 5, and (c) Example 8. Detailed Implementation
[0026] This invention provides a method for preparing a modified carbon felt electrode for an all-vanadium redox flow battery based on Joule thermal regulation, comprising the following steps: Step 1. Pretreatment: Heat-treat the raw carbon felt in air at 200℃~800℃ for 1s~15s to remove surface impurities and introduce oxygen-containing functional groups to obtain pre-oxidized carbon felt.
[0027] Step 2. Preparation of precursor solution: Dissolve the metal salt and nitrogen-containing organic ligand in a solvent and stir until completely dissolved to obtain the precursor impregnation solution; wherein the molar ratio of metal ions to ligands is (1:1) to (1:10).
[0028] Step 3. Immerse the pre-oxidized carbon felt in the precursor impregnation solution from Step 2, perform the impregnation treatment under sealed conditions, and then remove and dry it to ensure that the precursor is uniformly attached to the surface of the carbon felt fiber.
[0029] Step 4. Place the dried carbon felt between the two electrodes of the Joule heating device. Under inert gas protection, apply a pulsed current for instantaneous high-temperature shock, with the number of instantaneous high-temperature shocks being 1-3 times (e.g., Figure 1 As shown); by controlling the energizing parameters, the carbon felt is heated to 900℃~2000℃ within 0.1s~10s and maintained at that temperature for 0.1s~5s, then decreases at 500℃·s. -1 ~1000℃·s -1 The carbon felt electrode for the all-vanadium redox flow battery was obtained by cooling at a rate of Joule thermal regulation.
[0030] According to a preferred embodiment of the present invention, in step 1, the heat treatment in the air atmosphere is carried out in a constant flow mode, with a heating rate of 300°C·s. -1 ~500℃·s -1 This removes surface impurities and introduces oxygen-containing functional groups, while also improving hydrophilicity.
[0031] According to a preferred embodiment of the present invention, the solvent in step 2 is any one or more of ethanol, deionized water, methanol, DMF, etc., and the metal salt is one or more of Fe, Co, Ni, Zn, etc., with a concentration of 0.01M-0.05M in the precursor solution. The ligand is one or more combinations of 1,10-phenanthroline (Phen), melamine, melamine phosphate, and 2,2'-bipyridine. The precursor solution must be prepared and used immediately. When the transition metal is Fe or Co, the ligand is preferably 1,10-phenanthroline (Phen), and the molar ratio of the transition metal to the ligand is (1:3) to (1:5). When the transition metal is Ni, the ligand is preferably 2,2'-bipyridine. When the ligand is a combination of two of 1,10-phenanthroline (Phen), melamine, melamine phosphate, and 2,2'-bipyridine, the molar ratio of the main and auxiliary ligands is (2:1) to (2:5).
[0032] According to a preferred embodiment of the present invention, ultrasonic treatment is required when impregnating under sealed conditions, and the drying temperature is 60°C-80°C.
[0033] According to a preferred embodiment of the present invention, the inert gas is argon, and the gas flow rate is 200 mL·min. -1 ~500 mL·min -1 .
[0034] The present invention also provides a modified carbon felt electrode for a vanadium redox flow battery prepared by the method, wherein the electrode surface contains active sites, the active sites comprising an M-N4 structure; wherein M is selected from one or more of Fe, Co, Ni, Mn, and Zn.
[0035] The M-N4 structure is predominantly pyridine nitrogen-coordinated.
[0036] The modified carbon felt electrode prepared by the present invention contains active sites on its surface including M-N4 structures with pyridine nitrogen coordination as the main component and unsaturated coordinated M-N3 and M-N2 species, with the metal center M in a medium spin state or a high spin state.
[0037] The present invention also provides the application of the modified carbon felt electrode prepared by the above method in an all-vanadium redox flow battery.
[0038] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto.
[0039] In this embodiment of the invention, the customized Joule heating device used is the Saiyin pulse electric flash reactor FJH-2026Aplus.
[0040] Example 1: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 At 300℃·s in air -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0041] 2. Weigh 0.582 g of cobalt nitrate hexahydrate and 1.189 g of 1,10-phenanthroline (Phen), and dissolve them in 100 mL of deionized water and 100 mL of ethanol, respectively. Mix the two solutions and stir to obtain a precursor solution with a cobalt concentration of 0.01 M and a molar ratio of Co to ligand of 1:3.
[0042] 3. Immerse the pre-oxidized carbon felt in the precursor solution and sonicate it for 4 hours under sealed conditions. After removal, dry it in a vacuum drying oven at 80°C to obtain carbon felt loaded with the precursor.
[0043] 4. Place the dried carbon felt in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas was used. Capacitor discharge parameters were set, and a single pulse discharge was performed at 80V for 0.4s. The carbon felt reached a high temperature of approximately 1500℃ within about 0.1s, and then decreased at 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0044] Electrochemical performance testing: The modified carbon felt prepared in this embodiment was used as the working electrode, and cyclic voltammetry and performance tests at different current densities were performed in an electrolyte containing 3M H2SO4. The results showed that the potential difference (ΔEp) between the oxidation and reduction peaks was only 0.2V, much smaller than that of the unmodified carbon felt, and the peak current density was also significantly improved. At 300mA·cm -2 Charge-discharge tests were conducted at current density, achieving an energy efficiency of 75%, while the blank carbon felt achieved an efficiency of 300 mA·cm⁻¹. -2 Charge-discharge tests were conducted at current density, and the energy efficiency was only 72%. The modified electrode showed a 3% improvement in energy efficiency (EE) compared to the blank untreated carbon felt, and the battery performance was effectively improved, as shown in Table 1.
[0045] Example 2: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 At 300℃·s in air -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0046] 2. Weigh 0.808g Fe(NO3)3·9H2O and 1.1893g 1,10-phenanthroline, and dissolve them in 100mL of deionized water and 100mL of ethanol, respectively. Mix the two solutions and stir to obtain a precursor solution with an iron salt concentration of 0.01M and a molar ratio of Fe to ligand of 1:3.
[0047] 3. Immerse the pre-oxidized carbon felt in the precursor solution and sonicate it for 4 hours under sealed conditions. After removal, dry it in a vacuum drying oven at 80°C to obtain carbon felt loaded with the precursor.
[0048] 4. Place the dried carbon felt in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas was used. Capacitor discharge parameters were set, and a single pulse discharge was performed at 80V for 0.4s. The carbon felt reached a high temperature of approximately 1300℃ within about 0.1s, and then decreased at 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0049] Charge-discharge tests were conducted on the electrodes obtained in this embodiment at different current densities, and the results showed that the battery performance was effectively improved, with an energy efficiency of 300 mA·cm⁻¹. -2 At the current density, the efficiency is 76%, which is 4% higher than that of the blank untreated carbon felt, as shown in Table 1. In this example, Fe-N4 structure catalyst was prepared by Joule heating, and the transformation of Fe metal center from low spin to medium spin (S=3 / 2) was achieved within the Joule thermal shock temperature window.
[0050] Example 3: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0051] 2. Weigh 0.808 g of Fe(NO3)3·9H2O and 1.4417 g of 1,10-phenanthroline, dissolve them separately in 100 mL of ethanol and 100 mL of methanol, and mix to obtain 0.01 M Fe. 2+ The precursor solution.
[0052] 3. The pre-oxidized carbon felt was immersed in the precursor solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0053] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas was used. Three pulsed Joule heatings were performed at 80V, causing the carbon felt to reach 1100℃ within 0.1s, with each pulse lasting 0.2s and spaced 2s apart. This was followed by heating at 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0054] The electrode prepared in this embodiment was subjected to 300 mA·cm.-2 Charge-discharge tests were conducted at the specified current density, and the energy efficiency reached 77%, which is 5% higher than the energy efficiency (EE) of the blank untreated carbon felt, as shown in Table 1. In this example, a Fe-N4 structured catalyst mainly composed of pyridine nitrogen was prepared by Joule heating, and the results are as follows... Figure 3 As shown in (a), the transformation of the Fe metal center from low spin to medium spin (S=3 / 2) was achieved within this Joule thermal shock temperature window.
[0055] Example 4: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0056] 2. Weigh 0.808 g of Fe(NO3)3·9H2O and 1.982 g of 1,10-phenanthroline, dissolve them in 100 mL of methanol and 100 mL of deionized water respectively, then mix the solutions and stir evenly to obtain the precursor solution.
[0057] 3. The pre-oxidized carbon felt was immersed in the solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0058] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas. A single pulse discharge at 80V resulted in the carbon felt reaching 1400℃ in approximately 0.1s, with a rate of 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0059] The electrode prepared in this embodiment was subjected to 300 mA·cm. -2 Charge-discharge tests were conducted at current density, and the energy efficiency reached 77%, which is 5% higher than that of the blank untreated carbon felt, as shown in Table 1. Fe-N4 structure catalysts and modified carbon felts with medium or high spin state characteristics were also obtained, confirming the applicability of the process window.
[0060] Example 5: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces.2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0061] 2. Weigh 0.49g Fe(CH3COO)2·4H2O and 1.44g 1,10-phenanthroline, dissolve them in 100mL deionized water and 100mL methanol solution respectively, and then mix the two solutions to obtain a precursor solution with a metal salt concentration of 0.01M.
[0062] 3. The pre-oxidized carbon felt was immersed in the solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0063] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas was used. A single pulse discharge was performed at 80V, and the carbon felt reached 1500℃-1900℃ within approximately 0.1s, then decreased at a rate of 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0064] In this example, a Fe-N4 structured catalyst with pyridine nitrogen as the main component was prepared within a temperature window of 1500℃, and the results are as follows: Figure 3 As shown in (b), modified carbon felt with medium or high spin state characteristics was obtained. The cell confirmed the applicability of the process window, and the fabricated electrode achieved an efficiency of 300 mA·cm⁻¹. -2 Charge-discharge tests were conducted at current density, and the energy efficiency reached 77%-78%, which is 5%-6% higher than the energy efficiency (EE) of the blank untreated carbon felt.
[0065] Example 6: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0066] 2. Weigh 0.202 g of Fe(NO3)3·9H2O, 0.148 g of Zn(NO3)3·6H2O, and 0.792 g of 1,10-phenanthroline. Dissolve them in 50 mL of deionized water and 50 mL of methanol respectively, and then mix the two solutions to obtain a precursor solution with a total solvent volume of 100 mL.
[0067] 3. The pre-oxidized carbon felt was immersed in the solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0068] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas. A single pulse discharge at 80V causes the carbon felt to reach 1000℃-1300℃ in approximately 0.1s, with a rate of 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0069] The modified carbon felt electrode prepared at 1300℃ in this embodiment exhibits superior performance. Battery data confirms the applicability of the process window, and the prepared electrode achieves excellent performance at 300 mA·cm⁻¹. -2 Charge-discharge tests were conducted at current density, and the energy efficiency reached 76%, which is 4% higher than the energy efficiency (EE) of the blank untreated carbon felt.
[0070] Example 7: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0071] 2. Weigh 0.202 g of Fe(NO3)3·9H2O, 0.146 g of Co(NO3)2·6H2O, and 0.793 g of 1,10-phenanthroline. Dissolve them separately in 50 mL of deionized water and 50 mL of ethanol, respectively, and then mix the solutions. Make up the volume of the mixed solvent to 100 mL. The ratio of the total molar concentration of the metal salt to the molar concentration of the ligand is 1:4. The total concentration of the metal salt in the resulting precursor solution is 0.01 M.
[0072] 3. The pre-oxidized carbon felt was immersed in the solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0073] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas. A single pulse discharge at 80V causes the carbon felt to reach 1000℃-1200℃ within approximately 0.1s, with a rate of 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0074] In this embodiment, diatomic Fe-Co-N was prepared at 1200℃ by Joule heating. x The structured catalyst and the battery demonstrated the applicability of the process window; the fabricated electrode achieved an efficiency of 300 mA·cm⁻¹. -2 Charge-discharge tests were conducted at current density, and the energy efficiency reached 75%, which is 3% higher than the energy efficiency (EE) of the blank untreated carbon felt.
[0075] Example 8: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0076] 2. Weigh 0.29 g Ni(NO3)3·6H2O and 0.32 g 2,2'-bipyridine and dissolve them in 50 mL methanol and 50 mL LDM respectively to obtain 100 mL precursor solution, wherein the molar ratio of metal salt to ligand is 1:3 and the concentration of metal salt in the obtained precursor solution is 0.01 M.
[0077] 2. The pre-oxidized carbon felt was immersed in the solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0078] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas was used. A single pulse discharge was performed at 80V, causing the carbon felt to reach 1000℃-2000℃ within approximately 2 seconds, subsequently decreasing at 600℃·s. -1 The temperature was rapidly reduced. Ni-N was obtained under a pulsed temperature and time window of 1800℃ and 4s. x The structural catalyst and the modified carbon felt electrode with medium or high spin state characteristics were studied, and the results are as follows: Figure 3 As shown in (c).
[0079] The electrode prepared in this embodiment was used in a battery, confirming the applicability of the process window. The prepared electrode achieved a performance of 300 mA·cm⁻¹. -2 Charge-discharge tests were conducted at current density, and the energy efficiency reached 75%, which is 3% higher than the energy efficiency (EE) of the blank untreated carbon felt.
[0080] Example 9: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0081] 2. Using Fe(CH3COO)2·4H2O as the metal salt and 1,10-phenanthroline as the ligand, with melamine phosphate added as a secondary ligand, and a mixed solution of 200 mL deionized water and DMF in a 1:1 volume ratio, 0.49 g of Fe(CH3COO)2·4H2O, 1.586 g of 1,10-phenanthroline, and 0.896 g of melamine phosphate were weighed. The molar ratio of the metal salt to the primary and secondary ligands was 1:4:2, and the concentration of the metal salt in the resulting precursor solution was 0.01 M.
[0082] 3. The pre-oxidized carbon felt was immersed in the solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0083] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas. A single pulse discharge at 80V causes the carbon felt to reach 900℃-1200℃ within approximately 0.1s, with a rate of 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0084] In this embodiment, under extreme non-equilibrium thermal shock of Joule heating, the coordination shell undergoes drastic reconstruction. Partial N is replaced by P, forming a Fe-N3-P configuration. Since the electronegativity of P (2.19) is much lower than that of N (3.04), the covalent nature of the Fe-P bond is stronger, which breaks the perfect planar D4h symmetry of Fe-N4, leading to a significant reduction in the crystal field splitting energy (Δ0). Battery performance is effectively improved within a temperature window of 1100℃, confirming the applicability of the process window. The fabricated electrode achieves performance at 300 mA·cm⁻¹. -2Charge-discharge tests were conducted at current density, and the energy efficiency reached 74%, which is 2% higher than the energy efficiency (EE) of the blank untreated carbon felt.
[0085] Example 10: This embodiment provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 Place the carbon felt in air at 300°C for 30 seconds. -1 ~500℃·s -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0086] 2. Using Fe(CH3COO)2·4H2O as the metal salt and 1,10-phenanthroline as the ligand, melamine was also added as a secondary ligand. Specifically, 0.49g of Fe(CH3COO)2·4H2O, 1.586g of 1,10-phenanthroline, and 2.52g of melamine were weighed. The metal salt and the two ligands were dissolved in 100mL of deionized water and 100mL of DMF, respectively. After complete dissolution, the two solutions were mixed to obtain the precursor solution. The concentration of the metal salt solution was 0.01M, and the molar ratio of the metal salt to the primary and secondary ligands was 1:4:10.
[0087] 3. The pre-oxidized carbon felt was immersed in the precursor solution and ultrasonically soaked for 4 hours under sealed conditions. After removal, it was dried in a vacuum drying oven at 80°C to obtain the carbon felt loaded with the precursor.
[0088] 4. Place the carbon felt loaded with the precursor in a custom-made Joule heating device, with the electrodes in contact with both ends of the carbon felt, and introduce a flow rate of 500 mL / min. -1 High-purity argon gas. A single pulse discharge at 80V causes the carbon felt to reach 900℃-1200℃ within approximately 0.1s, with a rate of 500℃·s. -1 The temperature was rapidly reduced to a certain rate to obtain a modified carbon felt electrode.
[0089] In this embodiment, melamine decomposes at a temperature window of 1100℃ to produce pyridine N / graphite N doped into a carbon framework. An Fe-N4 structured catalyst was then prepared via Joule heating. The battery demonstrated the applicability of the process window, and the fabricated electrode achieved an operating temperature of 300 mA·cm⁻¹. -2 Charge-discharge tests were conducted at current density, and the energy efficiency reached 78%, which is 6% higher than the energy efficiency (EE) of the blank untreated carbon felt.
[0090] Comparative Example 1: This comparative example provides a method for preparing a modified carbon felt electrode for a vanadium redox flow battery, comprising the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 At 300℃·s in air -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0091] 2. Weigh 0.582 g of cobalt nitrate hexahydrate and 1.189 g of 1,10-phenanthroline (Phen), and dissolve them in 100 mL of deionized water and 100 mL of ethanol, respectively. Mix the two solutions and stir to obtain a precursor solution with a cobalt concentration of 0.01 M.
[0092] 3. Immerse the pre-oxidized carbon felt in the precursor solution and sonicate it for 4 hours under sealed conditions. After removal, dry it in a vacuum drying oven at 80°C to obtain carbon felt loaded with the precursor.
[0093] 4. The dried carbon felt is placed in a conventional tube furnace and heat-treated at 1000℃ for 2 hours under an argon atmosphere to obtain a modified carbon felt electrode.
[0094] The modified carbon felt electrode obtained in this comparative example was subjected to an A·cm temperature of 300 mA·cm. -2 Charge-discharge tests were conducted at current density, and the energy efficiency reached 73%.
[0095] Comparative Example 2: This comparative example provides a method for preparing a carbon felt electrode, including the following steps: 1. Cut a 5mm thick polyacrylonitrile-based carbon felt into (3×9) cm pieces. 2 At 300℃·s in air -1 The temperature was increased to 500℃ and then heat-treated for 15 seconds to obtain pre-oxidized carbon felt.
[0096] 2. Weigh 0.582 g of cobalt nitrate hexahydrate and 1.189 g of 1,10-phenanthroline (Phen), and dissolve them in 100 mL of deionized water and 100 mL of ethanol, respectively. Mix the two solutions and stir to obtain a precursor solution with a cobalt concentration of 0.01 M.
[0097] 3. Immerse the pre-oxidized carbon felt in the precursor solution and sonicate for 4 hours under sealed conditions. After removal, dry in a vacuum drying oven at 80°C to obtain a carbon felt electrode loaded with the precursor.
[0098] The electrodes obtained in Examples 1-10 under different pulse conditions were subjected to 300 mA·cm. -2 The energy efficiency was obtained by conducting charge and discharge tests and the results are summarized in Table 1.
[0099] Table 1. Summary of battery performance obtained in Examples 1-10; ; As can be seen from Table 1, the modified electrode prepared by the method provided in this invention has excellent electrochemical activity.
[0100] This invention utilizes an electrode prepared by Joule heating, which exhibits increased disorder in its coordination structure as shown by electron paramagnetic resonance signals. In the Fe-Phen complex, Fe... 3+ It forms an octahedral complex [Fe(Phen)3] with three Phen ligands. 3+ Phen is a strong-field ligand, Fe 3+ (d) 5 In a strong octahedral field, it tends to have a low-spin configuration (t2g). 5 (S=1 / 2). Low-spin Fe 3+ With short relaxation time and widened signal, its EPR signal is usually extremely weak or invisible, therefore... Figure 2 As shown, the blank (blank carbon felt) and the unheated sample (electrode obtained from Comparative Example 2) exhibit a stable baseline. Joule heating causes the Phen ligands to pyrolyze, and Fe... 3+ From the original [Fe(Phen)3] 3+ It is released in an octahedral coordination environment.
[0101] The modified electrodes obtained in Examples 3, 5, and 8 were characterized by XPS, and the results are as follows: Figure 3 As shown in (a) to (c), the main peaks in the N 1s spectra are located at 398.86 eV, 399.7 eV, and 399.84 eV, respectively, corresponding to pyridinic nitrogen and Fe-N. x It is the main nitrogen species, proving that Fe 3+ Anchored by pyridine N on the N-doped carbon framework, forming unsaturated Fe-N x Coordination structure or twisted structure. New coordination environment (Fe-N) x The ligand field strength of Fe is significantly weaker than that of Phen, resulting in Fe 3+ The electronic configuration transitions from low spin to medium spin (S=3 / 2) or high spin (S=5 / 2). The reaction is more complete under a 0.4s Joule pulse, resulting in more thorough Phen pyrolysis and Fe-N... x The anchoring is more complete, the proportion of medium and high spin Fe is significantly increased, and the EPR signal is stronger. This indicates that Joule heating facilitates the formation of Fe-N alloys dominated by pyridine nitrogen. x It has irreplaceable advantages in coordination structure and control of electronic spin states.
[0102] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all embodiments here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, characterized in that, Includes the following steps: Step 1. Pretreatment: The raw carbon felt is heat-treated in an air atmosphere to remove surface impurities and introduce oxygen-containing functional groups to obtain pre-oxidized carbon felt. Step 2. Preparation of precursor solution: Dissolve the metal salt and nitrogen-containing organic ligand in a solvent and stir until completely dissolved to obtain the precursor impregnation solution; In the precursor impregnation solution, the molar ratio of metal ions to ligands is (1:1) to (1:10). Step 3. Immerse the pre-oxidized carbon felt in the precursor impregnation solution and perform the impregnation treatment under sealed conditions. Then take it out and dry it. The precursor is evenly attached to the surface of the carbon felt. Step 4. Place the dried carbon felt between the two electrodes of the Joule heating device. Under inert gas protection, apply a pulsed current for instantaneous high-temperature impact, causing the carbon felt to heat up to 900℃~2000℃ within 0.1s~10s, and maintain this temperature for 0.1s~5s before reducing the temperature at 500℃·s. -1 ~1000℃·s -1 The modified carbon felt electrode was obtained by cooling at a certain cooling rate.
2. The method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation according to claim 1, characterized in that, In step 2, the metal salt is one or more of the corresponding salts of Fe, Co, Ni, and Zn; The nitrogen-containing organic ligand is one or a combination of 1,10-phenanthroline (Phen), melamine, melamine phosphate, and 2,2'-bipyridine.
3. The method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation according to claim 2, characterized in that, The metal salt is an Fe salt or a Co salt, and the nitrogen-containing organic ligand is 1,10-phenanthroline (Phen). The molar ratio of the metal ion to the nitrogen-containing organic ligand is (1:3) to (1:5).
4. The method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation according to claim 2, characterized in that, The metal salt is a Ni salt, and the ligand is 2,2'-bipyridine.
5. The method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation according to claim 2, characterized in that, The nitrogen-containing organic ligand is a combination of two of the following: 1,10-phenanthroline (Phen), melamine, melamine phosphate and 2,2'-bipyridine, with the molar concentration ratio of the two nitrogen-containing organic ligands being (2:1) to (2:5).
6. A method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation according to claim 1 or 2, characterized in that, In step 1, the heat treatment process is carried out in constant current mode at 300℃·s -1 ~500℃·s -1 The temperature is increased to 200℃~800℃ at a rate of 1s~15s.
7. A method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation according to claim 1 or 2, characterized in that, In step 3, ultrasonic treatment is required during impregnation under sealed conditions, and the drying temperature is 60℃~80℃.
8. A method for preparing a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation according to claim 1 or 2, characterized in that, In step 4, the instantaneous high-temperature impact is performed 1 to 3 times; The inert gas is argon, and the gas flow rate is 200 mL / min. -1 ~500 mL·min -1 .
9. A modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation, prepared by the method described in claim 1 or 2, characterized in that, The active sites on the surface of the modified electrode include an M-N4 structure with pyridine nitrogen coordination as the main component. M is selected from one or more of Fe, Co, Ni, Mn, and Zn; the metal center M is in a medium spin state or a high spin state.
10. The application of a modified carbon felt electrode for a vanadium redox flow battery based on Joule thermal regulation in a vanadium redox flow battery, wherein the modified electrode is prepared by the method described in claim 1 or 2.
